Crossing Limit Cycles Bifurcating from Two or Three Period Annuli in Discontinuous Planar Piecewise Linear Hamiltonian Differential Systems with Three Zones - Braga, Denis De Carvalho; Fonseca, Alexander Fernandes Da; Mello, Luis Fernando; Ribeiro, Ronisio Moises; Pessoa, Claudio Gomes [UNESP] (World Scientific Publishing, 2023)
The main topic studied in this article is the number of crossing limit cycles bifurcating from two or three period annuli in discontinuous planar piecewise linear Hamiltonian differential systems with three zones. With regard to the studies already published in the literature on this subject, we highlight the following five aspects of our work: (1) the expressions of the first order Melnikov functions for suitable perturbations of a piecewise Hamiltonian system with three zones separated by two parallel lines are obtained explicitly; (2) the way the Melnikov functions are obtained is different from what has already been done for similar studies; (3) the expressions of the Melnikov functions are used to estimate the number of crossing limit cycles that bifurcate simultaneously from period annuli under suitable polynomial perturbations; (4) since the piecewise Hamiltonian system studied here has no symmetry, the number of crossing limit cycles bifurcating from the period annuli is greater than or equal to those obtained in systems already studied; (5) unlike other similar studies, we present a concrete example of a piecewise linear near-Hamiltonian differential system in which the lower bound of the number of limit cycles that bifurcate from the period annuli is reached.
Keywords: Limit cycle; Melnikov function; period annuli; piecewise Hamiltonian differential system